Planning of graft size and 3D reconstruction using virtual reality technique in aortic valve reimplantation - Reid, Gregory; Gehweiler, Julian; Thieringer, Florian; Eckstein, Friedrich; Ferrari, Enrico; Gahl, Brigitta; Berdajs, Denis A. (Frontiers in Cardiovascular Medicine, 2023)
Objectives To evaluate applicability and feasibility of the virtual imaging technology for diagnosis and planning of the aortic valve sparing procedure. Methods Pre-operative electrocardiography-gated computed tomography images of 12 adult patients with aortic root pathology were used for 3D reconstruction of the aortic root geometry. The structural analysis was conducted with focusing on spatial architecture of key aortic root structures such as the three commissures, intervalvular triangles (IVT), as well as on morphology of the aortic root base (AoB) and of the sinotubular junction (STJ). Results In all included patients, the 3D mapping of aortic root (AoR) morphology was successfully performed. The pre-operative diameter of the AoB was 30.6 ± 2.6 mm and of the STJ 46.5 ± 7.5 mm (p < 0.001). Based on measured AoB diameter, the mean size of prosthesis used was 28.3 ± 1.37 mm. The planar arrangement of the three commissures was similar to an equilateral triangle where the three commissures were at similar distance for each individual sinus with 39.8 ± 6.64 mm for right, 37.5 ± 7.10 mm for left, and 39.2 ± 7.52 mm for non-coronary sinus (p = 0.72) subsequently. The similar height of the three IVT’s with 32.6 ± 5.87 mm for right, 33.6 ± 6.14 mm for anterior, and 31.7 ± 5.83 mm for left IVT (p = 0.73) was suggestive for all three commissures being positioned in the same plane. Consequently at reimplantation, the orientation of the three commissures followed the pattern of an equilateral triangle. Conclusion The reconstructed images revealed a detailed 3D anatomy of the aortic root, with the spatial arrangement of the intervalvular triangles, planimetric orientation of the commissures, as well as determination of the AoB and STJ diameters. Obtained information was successfully applied to pre-operative surgical planning. The reimplantation technique, the height of the reimplanted intervalvular triangles, as well as their orientation are crucial for achieving adequate aortic valve function.